Preventing disability through understanding international megatrends in Deaf bilingual education. Issue 2 (11th January 2008) - Munoz-Baell, I M; Alvarez-Dardet, C; Ruiz, M T; Ortiz, R; Esteban, M L; Ferreiro, E
Abstract : Background: Education is a basic prerequisite for d/Deaf people's health. Deaf education varies considerably from country to country and we still know very little about the reasons for such variation. Objective: To identify international megatrends that influence the current Deaf bilingual education move (Deaf Bilingual–Bicultural education; DBiBi) worldwide. Methods: Using the Delphi technique, 41 experts in d/Deaf education (nine Deaf, 32 hearing) from 18 countries identified, ranked, and rated international megatrends in DBiBi education. Results: The process revealed six main essential elements of the international implementation of DBiBi education and nine main barriers against it. The top five promoting forces in that list in order of priority were: (1) societal and political changes towards a growing acceptance of diversity and Deaf issues; (2) growing Deaf activism, self-awareness and empowerment; (3) scientific research in sign linguistics and bilingualism; (4) changes in the d/Deaf educational community; and (5) international cooperation. The top five hindering forces included: (1) the view of deafness as a medical condition with a technological solution; (2) phonocentrism and societal resistance to the unknown; (3) educational and d/Deaf educational policies; (4) DBiBi education weaknesses; and (5) invisibility, heterogeneity and underperformance of the d/Deaf population. Conclusion: The results of this study reveal that social/political changes and a medical/social model of Deaf people's health can promote or limit Deaf people's educational options much more than changes within the education system itself, and that a transnational perspective is needed in deciding how best to support DBiBi education at a national and local level in an increasingly globalised world.